Identification Of Inhibiting Factors for Road Construction Using Sem Application In Kaway XVI Sub-District - Muhammad Isya; Meidia Refiyanni; Muhajir Muhajir (International Journal of Engineering, Science and Information Technology, 2021)
Road construction is one thing that is always in line with technological advances and human thinking. Because the road is an important facility for humans, in order to reach an area. Continuous use of the road will reduce the service life of the road to the economic life of the road. To restore the service condition of the road, it is necessary to carry out road maintenance. Kaway XVI Sub-district is one of the connecting lines for Pidie Regency - West Aceh Regency, the road will continue to be built and maintained to support the agricultural and fishery sectors. The purpose of this study was to identify the inhibiting factors for road construction and maintenance as well as the relationship between these factors and indicators in Kaway XVI District using Structural Equation Modeling (SEM). The results of the study indicate that the quality factor has a positive effect on Spatial Planning and the Environment (TRL), and financing with a correlation number of 0.25 and 0.17. Regulations and Policies (PK) have a positive effect on financing of 0.60. Quantity has a positive effect on politics with a correlation number of 0.07. Politics has a positive effect on Regulations and Policies (PK) with a correlation number of 0.73, but negatively on TRL with a correlation number of -0.09. TRL has a positive effect on Human Resources (HR) with a correlation number of 0.81. HR has a significant positive effect on politics with a correlation of 0.67. Based on the research path diagram, the most decisive indicators both in quality and quantity for the construction and maintenance of roads in support of the Agriculture and Fisheries Sector are TRL, Financing, Politics and PK.